2006
DOI: 10.1186/1471-2458-6-98
|View full text |Cite
|
Sign up to set email alerts
|

Household and community socioeconomic and environmental determinants of child nutritional status in Cameroon

Abstract: Background: Undernutrition is a leading cause of child mortality in developing countries, especially in sub-Saharan Africa. We examine the household and community level socioeconomic and environmental factors associated with child nutritional status in Cameroon, and changes in the effects of these factors during the 1990s economic crisis. We further consider age-specific effects of household economic status on child nutrition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

35
129
0
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(170 citation statements)
references
References 33 publications
35
129
0
6
Order By: Relevance
“…A negative gender effect for male children is often reported but it tends to be small and does not necessarily show up significantly (Pongou et al, 2006). Our findings are similar since the coefficient associated with male gender is negative across specifications, albeit not always statistically significant (compare WAZ model for DHS with that for LSMS, Table 4).…”
Section: Child Nutritional Statussupporting
confidence: 75%
“…A negative gender effect for male children is often reported but it tends to be small and does not necessarily show up significantly (Pongou et al, 2006). Our findings are similar since the coefficient associated with male gender is negative across specifications, albeit not always statistically significant (compare WAZ model for DHS with that for LSMS, Table 4).…”
Section: Child Nutritional Statussupporting
confidence: 75%
“…Previous studies have shown a negative linear association between socioeconomic status and prevalence of childhood morbidity, because higher socioeconomic status is associated with healthy living conditions such as drinking water, access to appropriate sanitation and adequate nutrition (Pongou et al, 2006a). Results from the multivariate analyses show no statistical significant association between the household socio-economic status (asset index) and prevalence of fever.…”
Section: Resultsmentioning
confidence: 64%
“…Due to poverty, insufficient household sanitary conditions and other related factors, mothers might not be able to feed infants with enough clean breast milk so that mixed low quality foods or contaminated water are used instead (Pongou et al, 2006a, UNICEF, 1998. Furthermore, maternal nutritional status and health contribute to her inability to breast feed.…”
Section: Resultsmentioning
confidence: 99%
“…The potential strength of these underlying determinants of child nutrition was first raised at Alma-Ata in 1978 and later incorporated into the framework on child undernutrition developed by UNICEF in 1991 (14,37) . Although recent studies have shown a growing recognition that mothers and children reside in communities and that shared environmental contexts may be of key importance in improving child nutrition (38)(39)(40) , we are not aware of any corresponding research that has systematically quantified and investigated the influence of multiple aspects of the community environment on child nutritional status.…”
mentioning
confidence: 99%